Analysis Implementation Human and Organizational Performance Uses Evaluation Maturity Level in Animal & Nutrition Health Business - Sitohang, Noverto Marlin Suyono; Sudiarno, Adhithya (Newinera Publisher, 2025)
This study analyzes the implementation of Human and Organizational Performance (HOP) using maturity level assessment in the Animal & Nutrition Health business of PT Cargill Indonesia. The research focuses on evaluating the impact of HOP integration, including leadership, training, communication, incident management, and risk assessment programs, on safety culture and compliance. Data collection involved surveys, structured interviews, and incident trend analyses before and after HOP deployment. Findings reveal significant improvements in safety maturity levels, incident reduction, and the effectiveness of corrective and preventive actions. The study emphasizes the critical role of organizational culture in fostering safety compliance and offers recommendations for enhancing safety practices.